Ground deformation monitoring of landslides and precipitation-triggered mechanisms using GBInSAR - Yao, Di; Dai, Yingchao; Zhao, Ziwei (Frontiers in Earth Science, 2026)
Landslides are common in mountainous, hilly, and steep-slope regions, posing serious threats to human life, infrastructure, and ecological systems. Precipitation is a major triggering factor that can rapidly destabilize slopes by increasing moisture content and reducing soil shear strength. This study proposes an integrated landslide monitoring framework that combines satellite-borne InSAR for regional-scale detection, GB-InSAR for high-density dynamic monitoring, GNSS for precise three-dimensional ground deformation constraints, and rain-gauge observations for precipitation forcing characterization, with the aim of improving monitoring accuracy, spatiotemporal resolution, and early-warning capability. The results reveal a clear temporal correspondence between rainfall events and landslide displacement: during precipitation peaks (0.4 mm and 0.3 mm), displacement increased to approximately +25 mm and +35 mm, indicating direct rainfall-driven deformation responses. GB-InSAR further captures pronounced spatial heterogeneity across the landslide body, with maximum cumulative displacement reaching +656.3 mm and minimum displacement −1098.17 mm. GNSS measurements corroborate these deformation patterns, particularly during the acceleration stage when the trends derived from GNSS and GB-InSAR are highly consistent. Overall, multi-source evidence indicates that both short-duration intense rainfall and long-term precipitation accumulation contribute to landslide activity, with precipitation capable of inducing not only rapid displacement surges but also slower deformation under low-rainfall conditions. These findings provide a robust basis for landslide early warning and risk assessment in regions frequently affected by intense rainfall and sustained wet periods.